2010
DOI: 10.1186/cc9064
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of plasmatic cytokines and cystatin C during and after hemodialysis in septic shock-related acute renal failure

Abstract: IntroductionCystatin C could be a relevant residual glomerular filtration rate marker during hemodialysis (HD), and a high cytokine plasma (p) rate is associated with an increase in mortality during sepsis. To the best of our knowledge, cytokines and cystatin C kinetics during and after HD during sepsis have never been studied. In this study, we described p cytokines and cystatin C variations during and after hemodialysis in septic-shock patients with acute kidney injury (AKI).MethodsTen patients, from two ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In a previous study, 3 h of intermittent hemodialysis using a polymethylmethacrylate filter decreased cystatin C concentrations by 30 ± 7% [5]. This supports the hypothesis that in different types of renal replacement therapy serum cystatin C concentrations are reduced.…”
supporting
confidence: 77%
“…In a previous study, 3 h of intermittent hemodialysis using a polymethylmethacrylate filter decreased cystatin C concentrations by 30 ± 7% [5]. This supports the hypothesis that in different types of renal replacement therapy serum cystatin C concentrations are reduced.…”
supporting
confidence: 77%
“…It is apparent from blood chemistry analysis that PF4‐DTR mice suffered from more extensive kidney damage than WT mice, and this correlated with an increased bacterial burden in kidney. As acute kidney injury/failure contributes to the mortality of sepsis and septic shock , we found it interesting that PF4‐DTR mice had significantly more bacterial colonization than WT mice. It has been reported that platelets can encapsulate bacteria and facilitate their transport to immune effector cells , and that platelets can internalize and kill bacteria .…”
Section: Discussionmentioning
confidence: 90%
“…In the study by Mayeur et al . [ 37 ], 3 hours of intermittent hemodialysis decreased the Cys-C concentrations by 30%. This confirmed that the serum Cys-C concentrations are altered in patients who undergo RRT.…”
Section: Discussionmentioning
confidence: 99%